2007
DOI: 10.4049/jimmunol.179.5.2731
|View full text |Cite
|
Sign up to set email alerts
|

Novel Exosome-Targeted CD4+ T Cell Vaccine Counteracting CD4+25+ Regulatory T Cell-Mediated Immune Suppression and Stimulating Efficient Central Memory CD8+ CTL Responses

Abstract: T cell-to-T cell Ag presentation is increasingly attracting attention. In this study, we demonstrated that active CD4+ T (aT) cells with uptake of OVA-pulsed dendritic cell-derived exosome (EXOOVA) express exosomal peptide/MHC class I and costimulatory molecules. These EXOOVA-uptaken (targeted) CD4+ aT cells can stimulate CD8+ T cell proliferation and differentiation into central memory CD8+ CTLs and induce more efficient in vivo antitumor immunity and long-term CD8+ T cell memory responses than OVA-pulsed den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…These Tc-APCs can play both negative and positive modulations in antitumor immune responses by eliminating DC OVA and neighbouring Tc-APCs, and by stimulating OVA-specific CD8 + central memory T responses and antitumor immunity via targeting role of acquired pMHC I complexes (85). More recently, we have further shown that the exosome-targeted CD4 + T cell vaccine using OVAspecific or non-specific CD4 + T cells with uptake of OVA-specific DC-released exosomes expressing pMHC I complexes are capable of breaking CD4 + 25 + regulatory T (Tr) cell-mediated immune suppression and stimulating efficient antigen-specific CD8 + CTL response (86,87). However, CD4 + T cells with uptake of exosomes without expression of OVA-specific pMHC I complexes are unable to stimulate OVA-specific CD8 + CTL responses.…”
Section: Stimulatory Effect On Immune Responsesmentioning
confidence: 99%
“…These Tc-APCs can play both negative and positive modulations in antitumor immune responses by eliminating DC OVA and neighbouring Tc-APCs, and by stimulating OVA-specific CD8 + central memory T responses and antitumor immunity via targeting role of acquired pMHC I complexes (85). More recently, we have further shown that the exosome-targeted CD4 + T cell vaccine using OVAspecific or non-specific CD4 + T cells with uptake of OVA-specific DC-released exosomes expressing pMHC I complexes are capable of breaking CD4 + 25 + regulatory T (Tr) cell-mediated immune suppression and stimulating efficient antigen-specific CD8 + CTL response (86,87). However, CD4 + T cells with uptake of exosomes without expression of OVA-specific pMHC I complexes are unable to stimulate OVA-specific CD8 + CTL responses.…”
Section: Stimulatory Effect On Immune Responsesmentioning
confidence: 99%
“…12 Additional costimulations via 4-1BBL/4-1BB, OX40L/OX40 and CD40/CD40L interactions between DCs and CD8 1 T cells have also been found to promote effector CD8 1 T-cell responses during the priming phase 13,14 and CD8 1 Tm-cell development in the contraction phase. [15][16][17][18] However, whether these costimulatory events are also involved in priming and memory development in OVA-T EXO -stimulated CD8…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] To assess its therapeutic effect, C57BL/6 mice bearing 6-dayestablished OVA-expressing B16 melanoma BL6-10 OVA tumors were immunized with OVA-Texo in this study. We demonstrate that the OVA-Texo vaccine is unable to cure any mice bearing 6-day tumors, although OVA-Texo vaccination significantly reduces the average number of lung tumor colonies compared to the PBS control.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] We demonstrated that the OVA-Texo vaccine induces more efficient immunity than the DC vaccine and is capable of stimulating potent CD4 1 T cell-independent CTL responses and long-term antitumor immunity via IL-2/CD80 and CD40L signaling, counteracting regulatory T cellmediated immune suppression. [8][9][10] In addition, we also developed HIV-1 gp120-and Gag-specific T cell-based (gp120-Texo and Gag-Texo) vaccines using ConA-stimulated mouse CD8 1 T cells for the uptake of gp120-and Gag-specific DC-released EXOs. [11][12][13] We demonstrated that gp120-Texoand Gag-Texo-stimulated gp120-or Gag-specific CTL responses developed in transgenic HLA-A2 mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation